Conduction mechanisms and charge trapping control in SiO2 nanoparticle MIM capacitors. (20th June 2020) - Bheesayagari, Chenna R.; Pons-Nin, Joan; Orpella, Albert; Véliz, Bremnen; Bermejo, Sandra; Domínguez-Pumar, Manuel
Abstract: The objective of this paper is to present a charge trapping control method for MIM capacitors in which the dielectric is made of electrospray-deposited silica nanoparticles. The influence of the bias voltage on the impedance spectra of the devices is analyzed, as well as the main conduction mechanisms along the structure. The control method allows to monitor and control the long term drifts in the impedance of these devices, which are a result of the applied bias voltages. Graphical abstract: Image 1 Highlights: Conduction mechanisms in eMIMs with SiO2 nanoparticles are investigated through electrical characterization. Ohmic conduction is identified as the main conduction mechanism for low bias voltages applied. Poole-Frenkel emission is identified as the main conduction mechanism for high voltages applied. It is observed that voltage stress generates drifts in the impedance of the eMIMs. It is demonstrated that the drift of the C-V of eMIMs can be controlled successfully using a sigma-delta feedback loop.